Observations on Islamic Astronomy Research and Publications in Indonesia (2015-2024) - Diana Putri, Alfiah Rizky (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2024)
This article investigates research and publications related to Islamic astronomy, with a focus on Indonesia—the country with the largest Muslim population globally. The study examines scholarly works from Google Scholar over the past nine years (2015-2024), using filters for “astronomi islam” and “Islamic astronomy” using Publish or Perish application. The most frequently researched topics include the Islamic calendar, the new moon, and the Qibla. Surprisingly, despite the growth of Islamic astronomy in Indonesia, the number of studies on these topics has not increased substantially. To advance research, consider exploring automation and robotic systems, creating DIY tools, and leveraging image processing technology, machine learning, and deep learning.